Requirement of cell nucleus for Sindbis virus replication in cultured Aedes albopictus cells. - Erwin, C (1983)
The ability of Sindbis virus to grow in enucleated BHK-21 (vertebrate) and Aedes albopictus (invertebrate) cells was tested to determine the dependence of this virus upon nuclear function in these two phylogenetically unrelated hosts. Although both cell types could be demonstrated to produce viable cytoplasts (enucleated cells) which produced virus-specific antigen subsequent to infection. BHK cytoplasts produced a significant number of progeny virions, whereas mosquito cytoplasts did not. The production of vesicular stomatitis virus in mosquito cells was not significantly reduced by enucleation. That such a host function was not essential for vesicular stomatitis virus growth in insect cells is supported by the observation that the production of this virus by mosquito cells is not actinomycin D sensitive. This result agrees with a previously published report in which it was shown that Sindbis virus maturation in invertebrate cells is inhibited by actinomycin D, indicating a possible requirement for host cell nuclear function (Scheefers-Borchel et al., Virology, 110:292-301, 1981).